Las teorías del desarrollo y subdesarrollo en la sociología latinoamericana - Rios Burga, Jaime R. (2007)
Latin-American sociology inserts itself in and is different from social scientific creativity under the terms of dominance of the global corporate capitalism. The use and boundaries of its key categories and theories become increasingly rigorous and deep in accordance with the concepts, theories and models in each of its stages. The theories of development and underdevelopment are a typical example of this. How are development and underdevelopment theories constructed and changed between dependence and theoretical autonomy? This paper aims at reconstructing from a theoretical point of view, the most outstanding moments of the sociology of development and underdevelopment in Latin America. It is necessary to take stock and include its contribution to a comprehensive sociological theory of development as part of a social transcultural theory of development in the life of societies